Real-space observation of surface structuring induced by ultra-fast-laser illumination far below the melting threshold - Ch. Zaum (Nature Portfolio, 2021)
Abstract Intense short laser pulses are an intriguing tool for tailoring surface properties via ultra-fast melting of the surface layer of an irradiated target. Despite extensive studies on the interaction of femto-second laser interaction with matter, the initial steps of the morphological changes are not yet fully understood. Here, we reveal that substantial surface structure changes occur at energy densities far below the melting threshold. By using low-temperature scanning tunneling microscopy we resolve atomic-scale changes, i.e. the creation of nanosized adatom and vacancy clusters. The two cluster types have distinct non-linear fluence-dependencies. A theoretical analysis reveals their creation and motion to be non-thermal in nature. The formation of these atomistic changes, individually resolved here for the first time, recast our understanding of how surfaces respond to low-intensity ultra-short laser illumination. A visualization and control of the initial morphological changes upon laser illumination are not only of fundamental interest, but pave the way for the designing material properties through surface structuring.